INCORPORAÇÃO DE EXTRATO DE Campomanesia sessiliflora (O. Berg) Mattos EM FORMULAÇÃO COSMÉTICA - LOUREIRO, Raquel Parra; CASTRO, Thiago Luis Aguayo de; CARDOSO, Claudia Andrea Lima Cardoso (ANAIS DO ENIC, 2026)
.